Формування проектної культури студентів як передумова ефективної професійної діяльності - Гармаш, Сергій Володимирович (Univerzita Palackého v Olomouci, Czech Republic, 2010)
Forming of project culture of students is one of the main conditions for their effective professional activity. Some problems of modern higher education in Ukraine are analyzed in the article. The obvious conclusion is: "Culture, education, creative abilities of specialists are the factors, which define the success of professional activity".
Keywords: система вищої освіти; безперервність освіти; ринок праці; конкурентоспроможність; становлення особистості; духовна культура; project culture; effective professional activity